Social complexity in early medieval rural communities : the north-western Iberia archaeological record - Quirós Castillo, Juan Antonio, (Archaeopress archaeology., 2016)
This title presents an overview of the results of the research project DESPAMED funded by the Spanish Minister of Economy and Competitiveness. It discusses the theoretical challenges posed by the study of social inequality and social complexity in early medieval peasant communities in north-western Iberia.